Weak Wardowski contractive multivalued mappings and solvability of generalized phi-Caputo fractional snap boundary inclusions - Jafari, Hossein; Mohammadi, Babak; Parvaneh, Vahid; Mursaleen, Mohammad (Nonlinear Analysis: Modelling and Control, 2023)
In this paper, we introduce the notion of weak Wardowski contractive multivalued mappings and investigate the solvability of generalized ’-Caputo snap boundary fractional differential inclusions. Our results utilize some existing results regarding snap boundary fractional differential inclusions. An example is given to illustrate the applicability of our main results.